Metal-fluorocarbon based energetic materials - Koch, Ernst-Christian (Wiley-VCH ; John Wiley [distributor], 2012)
"The text opens with an historical overview followed by a thorough discussion of ignition, combustion and radiative properties. The next section explores the multifaceted military and civilian applications, as well as production and synthetic techniques. The critical importance of associated hazards, namely sensitivity, stability and ageing, are discussed in detail, and the whole is rounded off by a look at the future of this important and expanding field."--Provided by publisher.